2015
DOI: 10.5851/kosfa.2015.35.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-rigor Salting Levels on Physicochemical and Textural Properties of Chicken Breast Muscles

Abstract: This study was conducted to evaluate the effect of pre-rigor salting level (0-4% NaCl concentration) on physicochemical and textural properties of pre-rigor chicken breast muscles. The pre-rigor chicken breast muscles were de-boned 10 min post-mortem and salted within 25 min post-mortem. An increase in pre-rigor salting level led to the formation of high ultimate pH of chicken breast muscles at post-mortem 24 h. The addition of minimum of 2% NaCl significantly improved water holding capacity, cooking loss, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…is suggested that nitrite from celery juice showed an antioxidant effect similar to that of the synthetic nitrite. Lipid oxidation leads to rancidity of meat products [34], which in turn changes their nutritive value, flavor, and color [35]. TBARS value between 0.5 and 1.0 mg MD/kg of meat weight is considered as the lower threshold for observable oxidized odor and flavor of meat [20].…”
Section: Vbn and Tbars Content In Cured Pork Loinmentioning
confidence: 99%
“…is suggested that nitrite from celery juice showed an antioxidant effect similar to that of the synthetic nitrite. Lipid oxidation leads to rancidity of meat products [34], which in turn changes their nutritive value, flavor, and color [35]. TBARS value between 0.5 and 1.0 mg MD/kg of meat weight is considered as the lower threshold for observable oxidized odor and flavor of meat [20].…”
Section: Vbn and Tbars Content In Cured Pork Loinmentioning
confidence: 99%
“…Lipid oxidation is one of the most important changes during meat products storage and production [26]. It may change the color, aroma, flavor, texture, and nutritive values of meat products [8].…”
Section: Changes In Tbars Of Low-salt Frankfurters During Refrigeratementioning
confidence: 99%
“…In general, biochemical and physiochemical conditions of raw meat are important factors affecting salting effects on quality attributes of processed meat products, such as water-holding capacity and texture [ 5 ]. In this regard, it has been well documented that pre-rigor salting to maintain high pH and ATP content in pre-rigor skeletal muscles has been known to improve physicochemical properties of meat products, such as cooking yield, emulsion stability, and texture [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the practical use of pre-rigor salted meat, a previous study has found that the addition of least 2% NaCl should be required to guarantee the positive impacts of pre-rigor salting on water-holding capacity and protein solubility [ 5 ]. However, a recent study reported that pre-rigor salting with KCl was less effective compared to pre-rigor salting with NaCl at the same percentage concentration (2%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%